2003
DOI: 10.3386/w9665
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants and Consequences of Child Care Subsidies for Single Mothers

Abstract: This paper provides an analysis of child care subsidies under welfare reform. Previous studies of child care subsidies use data from the pre-welfare-reform period, and their results may not apply to the very different post-reform environment. We use data from the 1999 National Survey ofAmerica's Families to analyze the determinants of receipt of a child care subsidy and the effects of subsidy receipt on employment, school attendance, job search, and welfare participation. We analyze the impact on subsidy recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 10 publications
0
34
0
5
Order By: Relevance
“…Similar studies conducted in Turkey have also shown that families of disabled children do not receive adequate financial support and they experience financial difficulties [17,18]. Also, some of the studies have shown that parents with disabled children do not receive subsidies because they are unaware of the available services or believe that they are not eligible [22,23]. Most of the parents who were involved in the present study also stated that they were unsure about the present information on paying for the hearing aids (58%), for therapy (50.8%) and for child or respite care (55%).…”
Section: Discussionmentioning
confidence: 90%
“…Similar studies conducted in Turkey have also shown that families of disabled children do not receive adequate financial support and they experience financial difficulties [17,18]. Also, some of the studies have shown that parents with disabled children do not receive subsidies because they are unaware of the available services or believe that they are not eligible [22,23]. Most of the parents who were involved in the present study also stated that they were unsure about the present information on paying for the hearing aids (58%), for therapy (50.8%) and for child or respite care (55%).…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that the amount of social welfare and benefits (Wagenhals 1999) affects women's labor supply. Furthermore, other studies point to the importance of childcare and its increasing effect on single mothers' labor participation (Cascio 2009, Blau/Tekin 2007, Kornstadt/Thoresen 2007, Hank/Kreyenfeld 2000. Besides institutional aspects, sociodemographic factors play a decisive role in illustrating and explaining single mothers' labor participation.…”
Section: Introductionmentioning
confidence: 99%
“…Although many eligible children do not receive child-care assistance (Blau & Tekin, 2001;Child Care Bureau, 2002;Shlay, Weinraub, Harmon, & Tran, 2004), there are still many children who do. In 2002, it was estimated that more than 2 million children nationwide were receiving child-care subsidies through public funding programs (Adams & Rohacek, 2002).…”
Section: Introductionmentioning
confidence: 99%